The methanolic extract of Boesenbergia rotunda (L.) Mansf. and its major compound pinostrobin induces anti-ulcerogenic property in vivo: Possible involvement of indirect antioxidant action - Abdelwahab, S.I.; Mohan, S.; Abdulla, M.A.; Sukari, M.A.; Abdul, A.B.; Taha, M.M.; Syam, S.; Ahmad, S.; Lee, K.H. (Elsevier, 2011)
ETHNOPHARMACOLOGICAL RELEVANCE: Boesenbergia rotunda (L.) Mansf. has been used for the treatment of gastrointestinal disorders including peptic ulcer.